Smoking Behaviour in School Age Children: a Case Study on student of Vocational School in Panji District Situbondo Regency - Utami, Novitasari Dwi; Suhartini, Elly (Laboratorium Sosiologi FISIP Universitas Jember, 2018)
Smoking behavior in school-age children is a form of deviation from school regulations. This behavior results from interactions with the environment, especially with people who have consumed cigarettes. The main reasons teenagers smokes are curiosity in cigarettes and the desire to express men's identity through smoking. Families and peer groups generally provide a supportive environment for adolescents to smoke. The purpose of this study is to analyze and describe smoking behavior in school-age children. The research method uses descriptive, qualitative methods with purposive sampling techniques. This study found that families permit adolescents to smoke, and their schools do not strictly regulate smoking. Keywords: Smoking Behavior, Reasons for Smoking, Deviant Behavior. Keywords: Smoking Behavior, Reasons for Smoking, Deviant Behavior Referensi: Afrizal. 2015. Metode Penelitian Kualitatif. Jakarta: Rajawali Pers Dariyo, Agoes. 2004. Psikologi Perkembangan Remaja. Bogor: Ghalia Indonesia Denzin, Norman K & Yvonna S.Lincoln. Handbook Of Qualitative Research. Yogyakarta: Pustaka Pelajar Djamarah, Syaiful Bahri. 2014. Pola Asuh Orang Tua dan Komunikasi dalam Keluarga. Jakarta: Rineka Cipta Hasyim, Umar. 1984. Rokok Penyebar Maut. Surabaya: PT Bina Ilmu Jacky, M. 2015. Sosiologi Konsep, Teori dan Metode. Jakarta: Mitra Wacana Media Jaenudin, Ujam. 2015 Dinamika Kepribadian (Psikodinamik. Bandung: Pustaka Setia Lilly, Robert. 2015. Teori Kriminologi (Konteks & Konsekuensi). Jakarta: Prenadamedia Group Notoatmodjo, Soekidjo. 2007. Kesehatan Masyarakat Ilmu & Seni. Jakarta: Rineka Cipta. Pariwara, Intan. 2013. Detik-Detik Ujian Nasional Ekonomi. Partodihardjo, Subagyo. 2010. Kenali Narkoba dan Musuhi Penyalahgunaannya. Jakarta: ESENSI Erlangga Group Poltekkes Depkes Jakarta I. 2010. Kesehatan Remaja Problem dan Solusinya. Jakarta: Salemba Medika Ratrioso, Imam. 2008. Remaja Unggul Kamukah Itu?. Jakarta: Nobel Edumedia Salim, Agus. 2006. Teori dan Paradigma Penelitian Sosial. Yogyakarta: Tiara Wacana Santosa, Slamet. 1999. Dinamika Kelompok. Jakarta: Bumi Aksara Santrock, John W. 2007. Remaja. Jakarta: Erlangga Sudarsono, 1991. Kenakalan Remaja. Jakarta: PT Rineka Cipta